1998
DOI: 10.1017/s0890037x00044559
|View full text |Cite
|
Sign up to set email alerts
|

Sulfentrazone for Weed Control in Soybean (Glycine max)

Abstract: Field studies were conducted over 4 yr to evaluate weed control and soybean injury with sulfentrazone applied preplant incorporated or preemergence alone and in combination with imazaquin, metribuzin, or cloransulam. Sulfentrazone at 280 g ai/ha controlled yellow nutsedge, common waterhemp, ivyleaf morningglory, and velvetleaf 92 to 100% 56 days after planting (DAP). At 420 g/ha, sulfentrazone controlled giant foxtail 80 to 94% 21 DAP. Sulfentrazone controlled common ragweed 17 to 93% and common cocklebur 57 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
2
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 14 publications
3
34
2
3
Order By: Relevance
“…rudis in soybeans was sulfentrazone (Krausz et al 1998;Dirks et al 2000b;Hager et al 2002a;Nolte and Young 2002b;Krausz and Young 2003). Other preemergence herbicides reported to control A. tuberculatus var.…”
Section: Response To Herbicides and Other Chemicalsmentioning
confidence: 99%
“…rudis in soybeans was sulfentrazone (Krausz et al 1998;Dirks et al 2000b;Hager et al 2002a;Nolte and Young 2002b;Krausz and Young 2003). Other preemergence herbicides reported to control A. tuberculatus var.…”
Section: Response To Herbicides and Other Chemicalsmentioning
confidence: 99%
“…It has residual soil activity (Cobucci et al, 1998;Weber, 1993) with a half-life ranging from 6 to 12 months (Johnson and Talbert, 1993). Sulfentrazone provides effective weed control of many dicot and grass weeds in soybean (Krausz et al, 1998) and tobacco (Hancock, 1998;Walker et al, 1998). Differential cultivar response to sulfentrazone has been observed in soybean (Zhaohu et al, 1999) and southern pea [Vigna unguiculata (L.) Walp.]…”
Section: Journal Of Vegetable Crop Productionmentioning
confidence: 99%
“…This is consistent with other studies, which found that sulfentrazone (260 g•ai•ha −1 ) provided 87% control of giant foxtail (Setaria faberi Herrm.) [18] and imazethapyr (30 g•ai•ha ) decreased to 62% and 79%, respectively, control with s-metolachlor was ). Sulfentrazone + imazethapyr reduced foxtail biomass by 95%, but did not reduce foxtail density relative to the weedy control.…”
Section: Wild Mustardmentioning
confidence: 86%